Pengaruh Kesadaran Wajib Pajak, Lingkungan Sosial dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak UMKM (Studi pada Pelaku UMKM yang Terdaftar di Kantor Pelayanan Pajak Pratama Singaraja) - Desak Putu Erna Juliarmini; Sunitha Devi (Jurnal Akuntansi Profesi, 2022)
Attribution theory states taxpayer compliance comes from internal and external factors. Awareness is one of the important internal factors possessed by taxpayers. In addition to internal factors, the social environment and tax rates are also thought to influence taxpayer compliance.This study aimed to determine the effect of awareness, social environment and tax rates on MSMEs tax compliance. The population of this study was 6.120 MSMEs taxpayers registered with KPP Pratama Singaraja. The samples determination was conducted through random sampling method, so that a sample of 332 respondent was obtained. The data of this study were collected through a questionnaire was distributed via google form which was then processed through multiple linier regression analysis with the assistance of SPSS version 25. Results showed that, partially, the variables of awareness, social environment and tax rates have a positive impact on MSMEs taxpayers compliance.